Nagari Government Cooperation with Nomads Monitors in the Development of Nagari Sulit Air District of Solok - Ridho Yoliandri; Hendri Koeswara; Syamsurizaldi Syamsurizaldi (Universitas Medan Area, 2022)
Nomads in West Sumatra have a very big share in the development of the village, one of which is SulitAir, which has quite a several Nomads and has a nomadic organization called Sulit Air Sepakat (SAS) sothat it becomes one of the overseas assisted villages that must collaborate with nomads in the social,cultural and economic fields. It turns out that the implementation of cooperation has not yet beenrealized. There are problems such as coordination between parties collaborating with localgovernments and commitments from collaborating parties the purpose of this research is to describethe implementation of cooperation between the Nagari government and migrants in the developmentof Nagari Sulit Air in Solok Regency. This research uses the descriptive qualitative method. Datacollection techniques using interviews and documentation. The result shows that the implementationof the cooperation has not been implemented as a whole. In the initiation process, the collaboration hasbeen carried out well, starting from the beginning of the collaboration to the actors involved and therelationships between actors. Areas of cooperation are also carried out well with the submission ofwork plans but the areas that are cooperated have not been developed. There is nobody for organizingcooperation that is authorized to carry out this cooperation. The responsibility of the cooperationparties is still high but the commitment between the parties is reduced, one of which is due to thedifficulty in resolving land acquisition problems.